Wasp venom from Vespa magnifica acts as a neuroprotective agent to alleviate neuronal damage after stroke in rats - Hairong Zhao; Mei Wang; Xi Huang; Xiumei Wu; Huai Xiao; Fanmao Jin; Jiaming Lv; Jidong Cheng; Yu Zhao; Chenggui Zhang (Taylor & Francis Group, 2022)
Context Acute ischaemic stroke (AIS) is a major cause of disability and death, which is a serious threat to human health and life. Wasp venom extracted from Vespa magnifica Smith (Vespidae) could treat major neurological disorders. Objective This study investigated the effects of wasp venom on AIS in rats. Material and methods We used a transient middle cerebral artery occlusion (MCAO) model in Sprague-Dawley rats (260-280 g, n = 8-15) with a sham operation group being treated as negative control. MCAO rats were treated with wasp venom (0.05, 0.2 and 0.6 mg/kg, i.p.) using intraperitoneal injection. After treatment 48 h, behavioural tests, cortical blood flow (CBF), TTC staining, H&E staining, Nissl staining, TUNEL assay, immunohistochemistry (IHC) and ELISA were employed to investigate neuroprotective effects of wasp venom. Results Compared with the MCAO group, wasp venom (0.6 mg/kg) improved neurological impairment, accelerated CBF recovery (205.6 ± 52.92 versus 216.7 ± 34.56), reduced infarct volume (337.1 ± 113.2 versus 140.7 ± 98.03) as well as BBB permeability as evidenced by changes in claudin-5 and AQP4. In addition, function recovery of stroke by wasp venom treatment was associated with a decrease in TNF-α, IL-1β, IL-6 and inhibition activated microglia as well as apoptosis. Simultaneously, the wasp venom regulated the angiogenesis factors VEGF and b-FGF in the brain. Conclusions Wasp venom exhibited a potential neuroprotective effect for AIS. In the future, we will focus on determining whether the observed actions were due to a single compound or the interaction of multiple components of the venom.